ANALISIS KOMPARATIF TEORI PERKEMBANGAN MORAL LAWRENCE KOHLBERG DAN IBNU MASKAWAIH SERTA RELEVANSINYA DENGAN PENDIDIKAN KARAKTER MODERN - Lutfiyah, Siti Khumairotul; Muhid, Abdul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This research aims to comparatively analyze Lawrence Kohlberg and Ibn Maskawaih's moral development theory and its relevance in modern character education. Moral development is an important aspect in shaping learners' character related to social interaction and ethical values. Kohlberg emphasizes cognitive aspects and moral reasoning through stages of development, while Ibn Maskawaih emphasizes character building through habituation, emotional control, and spiritual values rooted in Islamic teachings. The research method uses a qualitative approach with a literature study. Researchers collected and analyzed primary and secondary literature related to the theories of the two figures, and conducted a systematic content analysis. The results of the analysis show that Kohlberg focuses on developing moral reasoning skills and the concept of justice in a secular manner, while Ibn Maskawaih places the formation of virtuous character within the Islamic spiritual framework and holistic happiness (sa'adah). Significant differences also exist in the role of religion and the integration of emotions in the moral process. Both theories are complementary and can be integrated to support moral education that is holistic, contextual, and relevant to the challenges of the modern world.